Effect of processing and end groups on the crystal structure of polypeptoids studied by cryogenic electron microscopy at atomic length scales. Issue 23 (29th May 2019) - Jiang, Xi; Xuan, Sunting; Kundu, Joyjit; Prendergast, David; Zuckermann, Ronald N.; Balsara, Nitash P.
Abstract : Imaging two dominant crystal motifs in self-assembled polypeptoid crystalline nanosheets with 2.1 Å resolution. Abstract : Cryogenic electron microscopy at atomic length scales was used to study the structure of self-assembled crystalline nanosheets obtained from a series of polypeptoids with the same chain architecture but with different end groups. While long-range order is enhanced by slowing down the self-assembly process, the dominant crystalline motif was found to be a sensitive function of both processing details and end group chemistry. In some cases, adjacent rows of polypeptoid molecules adopt anti-parallel V-shaped side chain conformations. In other cases, adjacent rows of polypeptoid molecules adopt parallel V-shaped side chain conformations. Interestingly, the unit cell is rectangular in both cases with dimensions a = 4.5 Å and c = 50 Å. In all cases, long-range order, quantified by the average number of concatenated unit cells of the same type, is more prevalent along the a direction.